2015
DOI: 10.1093/mnras/stv2582
|View full text |Cite
|
Sign up to set email alerts
|

Light versus dark in strong-lens galaxies: dark matter haloes that are rounder than their stars

Abstract: We measure the projected density profile, shape and alignment of the stellar and dark matter mass distribution in 11 strong-lens galaxies. We find that the projected dark matter density profile -under the assumption of a Chabrier stellar initial mass function -shows significant variation from galaxy to galaxy. Those with an outermost image beyond ∼ 10 kpc are very well fit by a projected NFW profile; those with images within 10 kpc appear to be more concentrated than NFW, as expected if their dark haloes contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 114 publications
4
19
0
Order By: Relevance
“…The lenses with large misalignment (∆PA> 12 deg) also have relatively larger (γ ext 0.05) external shear within the sample. This result is consistent with previous studies (Kochanek 2002;Ferreras et al 2008;Treu et al 2009;Gavazzi et al 2012;Sluse et al 2012;Bruderer et al 2016;Shajib et al 2018). The absence of systems with large misalignment angle and low external shear is consistent with the prediction of galaxy formation models that highly misaligned orbits in isolated galaxies are unstable and thus rare (e.g., Adams et al 2007;Debattista et al 2015).…”
Section: Appendix A: Mass and Light Alignmentssupporting
confidence: 92%
“…The lenses with large misalignment (∆PA> 12 deg) also have relatively larger (γ ext 0.05) external shear within the sample. This result is consistent with previous studies (Kochanek 2002;Ferreras et al 2008;Treu et al 2009;Gavazzi et al 2012;Sluse et al 2012;Bruderer et al 2016;Shajib et al 2018). The absence of systems with large misalignment angle and low external shear is consistent with the prediction of galaxy formation models that highly misaligned orbits in isolated galaxies are unstable and thus rare (e.g., Adams et al 2007;Debattista et al 2015).…”
Section: Appendix A: Mass and Light Alignmentssupporting
confidence: 92%
“…The inner dark matter slope is notably steeper than the predicted logarithmic slope of unity for an NFW profile at small radii. A mean slope of γ PL dm (0.5 R eff , R eff ) ∼ 1.49 is well consistent with both observations (e.g., Sonnenfeld et al 2012;Cappellari et al 2013;Oguri et al 2014;Bruderer et al 2016) and published simulations (e.g., Johansson et al 2012;Remus et al 2013). Fig.…”
Section: Inner Slope Estimates Of the Dark Matter And The Stellar Dissupporting
confidence: 90%
“…This may also explain the systematically lower ellipticity ratios between the luminous and the total matter distributions of the simulated galaxies. However, it is also noteworthy to point out that recent lensing studies that have either applied non-parametric lens modelling (e.g., Bruderer et al 2016) or adopted novel techniques to extract galaxy morphology data from adaptive optics observations (e.g., Rusu et al 2016) found that the total matter distributions are systematically rounder than the stellar distributions in central regions of early-type galaxies, in agreement with our simulation results.…”
Section: Shape Of Luminous and Total Mattersupporting
confidence: 90%
“…In some cases it may be reasonable to put priors on the lens galaxy ellipticity and orientation based on the light profile (e.g., Bolton et al 2008), but in lensing there is not always a strong relation between the light and mass (Bruderer et al 2015, and references therein). Therefore we do not place any priors on the lens galaxy parameters.…”
Section: Fitting Mock Lensing Observablesmentioning
confidence: 99%